Critical success factors for ICT integration in agri-food sector: pathways for decarbonization and sustainability - Sharma, Isha; Sarkar, Bishal Dey; Jagtap, Sandeep (Elsevier, 2025)
A decarbonized agri-food sector may provide consumers with nutritious, secure, and reasonably priced food with a lower carbon impact. Decarbonizing the agri-food sector is intricate and necessitates a holistic strategy. Technological advancements, like Information and Communication Technologies (ICT), might be the solution. This study analyses the critical success factors (CSFs) for ICT integration in the agri-food sector in the Western and North Western States of India based on empirical data collected and analyzed. The study proposes a framework that determines and ranks the significant factors for ICT integration in the agri-food sector to achieve the decarbonization goals by utilizing the fuzzy evidential reasoning approach (FERA) and the evidential reasoning approach (EFA). The factors are examined based on the Technological, Organization, and Environmental (TOE) criteria. The results show that the most significant factors contributing to the effective implementation of ICT in the agri-food sector are continuous innovation and R&D, supportive policies and regulations, and cost-effectiveness. The results will assist managers and decision-makers in creating effective policies and making knowledgeable choices that will support sustainable growth in the agri-food industry by lowering carbon emissions through effective ICT integration.
Keywords: Decarbonization; Sustainability; Fuzzy evidential reasoning approach (FERA); Critical success factors; TOE framework; 40 Engineering; 4011 Environmental Engineering; Metabolic and endocrine; 2 Zero Hunger